Development and Characterization of Natural Product Derived Macromolecules Based Interpenetrating Polymer Network for Therapeutic Drug Targeting - Biswas, Avirup; Mondal, Sancharee; Das, Sanjoy Kumar; Bose, Anindya; Thomas, Sabu; Ghosal, Kajal; Roy, Sudeep; Provaznik, Ivo (ACS omega, 2021)
Interpenetrating polymer network (IPN)-based bead formulations were exploited by cross-linking different hydrophilic polymers in different combinations and at different ratios. Polyvinyl alcohol, xanthan gum, guar gum, gellan gum, and sodium alginate (Na-alginate) were used in this work as hydrophilic polymers to enhance the solubility of diclofenac sodium and also to target the delivery at preferred locations. IPN beads based on polysaccharides were prepared by the ionic gelation method. Differential scanning calorimetry, powder X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy data showed that the IPN microbeads solubilized and encapsulated the drug within the network. We found over 83% encapsulation efficiency of the drug delivery system for the drug, and this efficiency increased with the concentration of the polymer. Ex vivo experiments using the goat intestine revealed that the IPN microbeads were able to adhere to the intestinal epithelium, a mucoadhesive behavior that could be beneficial to the drug pharmacokinetics, while in vitro experiments in phosphate buffer showed that the IPN enabled significant drug release. We believe that these IPN microbeads are an excellent drug delivery system to solubilize drug molecules and ensure adhesion to the intestinal wall, thereby localizing the drug release to enhance bioavailability of poorly soluble drugs.